Synchrotron X-ray studies on polyamide composites prepared by reactive injection molding - Dencheva, Nadya Vasileva (2014)
Semicrystalline polyamide 6 (PA6) and composites on its basis are among the most frequently used polymer materials for highly demanding applications. The performance of these composites depends on the crystalline structure of the PA6 matrix in which two crystalline forms most frequently coexist: α- and γ-polymorphs. This work reports on the crystalline structure of a variety of composite materials produced by in-mold reactive polymerization of caprolactam in specially designed semi-automatic equipment for reactive processing of nylons (NYRIM), carried out in the presence of particulate mineral reinforcements (natural or-ganically treated aluminum silicates and synthetic titanosilicates), PA6 oriented monofilaments and textile structures of glass fibers. The morphology and the crystalline structure of all composites were studied by syn-chrotron X-ray diffraction. Transcrystalline PA6 layer was observed in all fibrous PA6 laminates whose struc-ture fine crystalline structure was accessed.